"It's Global Warming, Stupid": Aggressive Communication Styles and Political Ideology in Science Blog Debates About Climate Change. (December 2020) - Yuan, Shupei; Lu, Hang
The current study examined the effects of aggressive communication styles on individuals' pro-environmental behavioral intentions. Two underlying mechanisms—psychological reactance and expectancy violation—as well as the moderating role played by political ideology were investigated. An online experiment ( N = 423) was conducted and the results showed that more aggressive style was more likely to trigger psychological reactance and violation of expectation, liberals responded more negatively to the aggressive message than conservatives, and expectancy violation was an important mediator. The findings provide explanations for how communication styles affect individuals' information processing and offer implications regarding selecting communication styles wisely.